Akuntansi Karbon dan Akuntabilitas Lingkungan dalam Perspektif Ekonomi Syariah - Zakiyah, Kuni; Yuliastuti, Rika (Institut Agama Islam YPBWI Surabaya, 2025)
Climate change has become a global issue that demands active involvement across various sectors, including accounting. Within the context of Islamic finance, carbon accounting serves as an essential instrument to realize ecological responsibility in alignment with the principles of maqashid al-shariah. This article aims to construct a conceptual framework for sharia-based carbon accounting, examine its implications for organizational decision-making, and analyze it within the perspective of Islamic economics to prevent the capitalization of the environment solely for business interests. Using a literature review and normative analysis approach, this study concludes that sharia-compliant carbon accounting can serve as an instrument of environmental accountability that promotes the application of Islamic ethics in sustainable business governance.